Degradome of the Interverteral Disc. Issue 1 (April 2016) - Tam, Vivian; Solis, Nestor; Overall, Christopher; Klein, Theo; Cheung, Kenneth M. C.; Cheah, Kathryn S. E.; Chan, Danny
Introduction: The intervertebral disc (IVD) is a complex structure consisting of the nucleus pulposus (NP), annulus fibrosus (AF) and cartilage endplates (EP), which work collectively for proper disc function. Both aging and degeneration alter the biochemical and mechanical function of the IVD – potentially leading to degeneration, which is still not fully understood. In human IVD, sparsely populated cells embedded within the matrix are responsible for the production of matrix, of which its upkeep is important for disc maintenance and function. However, the processes involved with disc maintenance in the non-degenerated condition, versus those that lead to IVD degeneration remain to be identified. Moreover, the presence of reported enzymes in the IVD are likely to contribute to matrix changes by cleaving proteins, thereby altering protein function, and potentially disc function. Studying the degradome of the IVD may identify fragmented proteins and enzymes that degrade these proteins and elucidate events that occur in IVD maintenance versus IVD degeneration, of which cannot be identified by conventional mass spectrometry techniques. Here, we examined the degradome of non-degenerated and degenerated IVD using Terminal Amine Isotopic Labeling of Substrates (TAILS) which facilitates the enrichment of N-termini peptides of degraded protein fragments. Material and Methods: NP and AF isolated from three non-degenerated IVD and three degenerated IVD were snap frozen and pulverized in liquid nitrogen. Samples were extracted with 1% SDS with protease inhibitor. N-terminal peptides were enriched using the TAILS method. Briefly, each sample was individually labeled with a Tandem Mass Tag (TMT) and mixed together at equal ratios. The pooled sample was digested with trypsin, and the peptides containing free amines were depleted by polymerization. Samples were analyzed by mass spectrometry (Bruker Daltonics Impact II QTOF), and data analyzed using Scaffold Software. Results: Sixty-one peptides (corresponding to 61 protein fragments) were identified in the NP samples. Degenerate NP had more cleaved matrix proteins, including fibronectin, COMP, and lubricin. In non-degenerated NP, the cleaved proteins included collagen II and lysozyme. Ninety-one peptides (corresponding to 91 protein fragments) were identified in the AF samples. Degenerated AF had more cleaved matrix proteins including COMP and fibronectin, in addition to CILP and HAPLN1. Non-degenerate AF had more cleaved collagen I, II, and VI. Conclusion: In degenerate AF and NP, the presence of more cleaved matrix proteins, particularly those that are associated with stability, can potentially lead to alterations in the mechanical properties and function of the IVD. Conversely, the cleaved proteins in the non-degenerate tissue could indicate turnover of proteins associated with maintaining a non-degenerate disc environment (such as collagen II in NP, and collagens I and II in AF). Understanding the degenerative process and maintenance of the disc via analysis of the degradome can highlight events that are occurring in health and in degeneration, in addition to the identification of enzymes that cleave these proteins, of which are currently in progress. Acknowledgment: This work was supported by the Research Grants Committee of Hong Kong–Theme-based Research Scheme (T-12–708/12N).